THE MECHANISM OF CHILDREN'S COGNITIVE PROCESS - Yuldasheva Dilafruz Mahammadaliyevna; Kholmatova Yodgoroy Bakhtiyorjon kizi (Zeta Repository, 2023)
The article talks about the features of the formation of cognitive processes in preschool children. The structure of the cognitive sphere and a brief description of the development of processes such as perception, memory, imagination, thinking and also attention are being studied.